A meta-analysis of workplace exclusion on employee work behavior in the Chinese context - Zhengdong Li; Zhengdong Li; Wenyu Li (Frontiers in Psychology)
This study explores the impact of workplace exclusion on employee work behavior in the Chinese context. By employing the doctrine of the mean value orientation and self-consistency theory, the study aims to enhance the understanding of local workplace exclusion in China and its effects on employees’ work behavior. Furthermore, the study investigates the moderating role of employee types, data collection points, and data sources. Our meta-analysis included 24,662 participants from 72 independent samples. The findings indicate that workplace exclusion significantly influences employees’ positive work behavior negatively and their negative behavior positively. Moreover, the study identifies a moderating effect based on employee type (knowledge vs. non-knowledge type), revealing a stronger relationship between workplace exclusion and employee work behavior among knowledge employees. Examining the data collection point (cross-sectional vs. non-cross-sectional) as another moderating factor, the study demonstrates a stronger relationship between workplace exclusion and employee work behavior in the cross-sectional mode. Additionally, the data source (self-evaluation vs. superior evaluation plus self-evaluation) plays a moderating role, with employee self-evaluation strengthening the relationship between workplace exclusion and employee work behavior.